Cultural adaptation and validation of “aging voice index” in Bengali - Adhikary, Rumela; Biswas, Saheli; Chatterjee, Indranil (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Changes in voice due to aging impact the ability to use one’s voice to communicate in all situations and can decrease their quality of life. The primary objective of this study was to transadapt the aging voice index (AVI) in Bengali (AVI-B) for the Bengali population to help in better comprehension by the patient rating the AVI scale. Ten older adults with voice disorder were asked to fill the AVI-E and AVI-B simultaneously to check the homogeneity of AVI-B. Establishment of kappa co-efficient between AVI-E and AVI-B was done. Wilcoxon test was done to evaluate the differences between pre and post therapeutic results. Kappa correlation for content validity was 0.81. The parameters of doctor speech, grade of grade, roughness, breathiness, asthenia, strain, and instability (GRABASI) scale and voice handicap index (VHI)-10 scale were mild to moderately correlated to the AVI-B (p>0.05). Inter class correlation for test-retest reliability was 0.933. Pre to post AVI-B scores were reduced when the participants were given a period of straw phonation therapy treatment. The AVI-B is a valid and reliable quality of life assessment for older adults with voice disorder and with native language as Bengali.